2021
DOI: 10.3389/fnins.2021.656856
|View full text |Cite
|
Sign up to set email alerts
|

Right Inferior Parietal Lobule Activity Is Associated With Handwriting Spontaneous Tempo

Abstract: Handwriting is a complex activity including motor planning and visuomotor integration and referring to some brain areas identified as “writing centers.” Although temporal features of handwriting are as important as spatial ones, to our knowledge, there is no evidence of the description of specific brain areas associated with handwriting tempo. People with multiple sclerosis (PwMS) show handwriting impairments that are mainly referred to as the temporal features of the task. The aim of this work was to assess d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Higher fMRI activation was associated with lower tremor severity Alahmadi et al, 2021 14 people with RRMS 14 HC To squeeze a rubber ball with varying grip force levels using the right hand In response to the variable grip force task, fMRI activation was increased in MS vs HC both in anterior and posterior BA4. However, non-linear analysis showed abnormal non-linear responses to increasing grip forces in MS in posterior BA4 Bonzano et al, 2021 18 people with MS 18 HC Writing a sentence in cursive Hand-writing elicited fMRI activity was lower in people with MS vs HC in temporal, parietal, insular and basal ganglia regions. Preserved fMRI activity in these regions was associated with better writing performances Strik et al, 2021 28 people with RRMS 17 HC To follow a target force line by squeezing and releasing the right fingers, or by pulling up and down the right foot During the lower limb force matching task, lower fMRI activity was detected in people with MS vs HC in cerebellar, occipital and superior parietal cortices.…”
Section: Using Fmri To Explore Ms-related Functional Reorganization W...mentioning
confidence: 90%
See 1 more Smart Citation
“…Higher fMRI activation was associated with lower tremor severity Alahmadi et al, 2021 14 people with RRMS 14 HC To squeeze a rubber ball with varying grip force levels using the right hand In response to the variable grip force task, fMRI activation was increased in MS vs HC both in anterior and posterior BA4. However, non-linear analysis showed abnormal non-linear responses to increasing grip forces in MS in posterior BA4 Bonzano et al, 2021 18 people with MS 18 HC Writing a sentence in cursive Hand-writing elicited fMRI activity was lower in people with MS vs HC in temporal, parietal, insular and basal ganglia regions. Preserved fMRI activity in these regions was associated with better writing performances Strik et al, 2021 28 people with RRMS 17 HC To follow a target force line by squeezing and releasing the right fingers, or by pulling up and down the right foot During the lower limb force matching task, lower fMRI activity was detected in people with MS vs HC in cerebellar, occipital and superior parietal cortices.…”
Section: Using Fmri To Explore Ms-related Functional Reorganization W...mentioning
confidence: 90%
“…( Rocca et al, 2009 , Wegner et al, 2008 ) Also, a decreased deactivation of the motor circuit ( Manson et al, 2008 , Petsas et al, 2013 ) and increased deactivation of the default-mode network system was found during motor tasks. ( Petsas et al, 2013 ) Overall, patterns of increased fMRI activations, both in primary motor and associative regions, were obtained by studies investigating motor functions using different tasks, such as motor imagery, ( Tacchino et al, 2017 ) hand writing, ( Bonzano et al, 2021 , Saini et al, 2004 ) grip force ( Alahmadi et al, 2021 , Strik et al, 2021 ) and joystick tasks. ( Boonstra et al, 2020 ) A few studies also detected selective associations between increased motor fMRI activity and higher upper limb ( Reddy et al, 2002 , Wegner et al, 2008 ) or lower limb ( Ciccarelli et al, 2006 ) clinical impairment.…”
Section: Using Fmri To Explore Ms-related Functional Reorganization W...mentioning
confidence: 99%
“…Previous studies have suggested that the right PFC is associated with inhibitory control of executive function [13,14] and that the middle PFC is associated with executive function switching [15]. A previous study that focused on tempo when Psych 2023, 5 writing letters showed a relationship with the right inferior parietal lobule [16]. However, the localization of activity within the PFC in relation to the continuous drawing of complex figures, such as letters, has not been clarified.…”
Section: Introductionmentioning
confidence: 94%
“…Bilaterally, the inferior parietal lobule also plays roles in sound perception and auditory memory despite the primary auditory cortex being in Heschl's gyrus in the superior temporal lobe ( 103 , 113 ), saccadic eye movements ( 114 ), egocentric decision-making ( 60 ), and emotional empathy ( 34 ). The left inferior parietal lobule is involved in speech and language processing ( 108 ) and reading and writing ( 75 ), while the right inferior parietal lobule is responsible for natural handwriting tempo ( 115 ).…”
Section: Regional Brain Anatomy and Associated Post-concussion Symptomsmentioning
confidence: 99%